Sistem Informasi Geografis Pencarian Lokasi Agen Bus dan Travel Terdekat di Kota Semarang Berbasis Mobile dengan Metode Dijkstra - M. Rizki Kurniawan; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Nowadays, the mobility of people who travel to a place through road transportation is increasing, either private vehicle or public transportation services. By the high intensity of use the road transportation, especially the road transportation service in Semarang, in this cases are bus and travel, it makes the transportation service users often confused in determining transportation agency to be used, especially if user is in hurry. Therefore, transportation user need a mobile application that can provide bus or travel transportation agency locator services which nearby user location and provide destination route which is expected. The Bus and Travel agency – Based Applications Mobile Locator Using Dijkstra Method is the ultimate solution in the search of bus and travel agency in Semarang. The purpose of development this application is developing a search guidance system of bus and travel agency location which nearby user location that can provide an efficient route and save the time. The Bus and Travel agency – Based Applications Mobile Locator is implemented using ionic framework that runs on Android. Sqlite as the media storage of this, allows user to perform agency data management. In Addition, it is supported by the relevance of agency data which is obtained from Department of Transportation, Communication, and Information Central of Java and transportation magazine site. The use of Google Maps API supports search location using Dijkstra Method in search of bus and travel agency, that expected to facilitate the users find travel or bus agency as expected, and its information that’s already available.